Therapeutic Potential for Beta-3 Adrenoreceptor Agonists in Peripheral Arterial Disease and Diabetic Foot Ulcers - Cameron J. F. Evans; Sarah J. Glastras; Owen Tang; Gemma A. Figtree (Biomedicines, 2023)
Annually, peripheral arterial disease is estimated to cost over USD 21 billion and diabetic foot disease an estimated at USD 9–13 billion. Mirabegron is a TGA-approved beta-3 adrenoreceptor agonist, shown to be safe and effective in the treatment of overactive bladder syndrome by stimulating bladder smooth muscle relaxation. In this review, we discuss the potential use of beta-3 adrenoreceptor agonists as therapeutic agents repurposed for peripheral arterial disease and diabetic foot ulcers. The development of both conditions is underpinned by the upregulation of oxidative stress pathways and consequential inflammation and hypoxia. In oxidative stress, there is an imbalance of reactive oxygen species and nitric oxide. Endothelial nitric oxide synthase becomes uncoupled in disease states, producing superoxide and worsening oxidative stress. Agonist stimulation of the beta-3 adrenoreceptor recouples and activates endothelial nitric oxide synthase, increasing the production of nitric oxide. This reduces circulating reactive oxygen species, thus decreasing redox modification and dysregulation of cellular proteins, causing downstream smooth muscle relaxation, improved endothelial function and increased angiogenesis. These mechanisms lead to endothelial repair in peripheral arterial disease and an enhanced perfusion in hypoxic tissue, which will likely improve the healing of chronic ulcers.